Rocket emissions representation in atmospheric air‐quality models: The short‐range atmospheric transport and reaction of gases released by solid propellant engines. (29th November 2018) - Schuch, Daniel; Fisch, Gilberto
Abstract : One risk associated with rocket‐launching activities is the inhalation of exhaust gases, which can occur either in the vicinity of the launch pad or, depending on the way these gases are transported and dispersed through the atmosphere, at locations far from the launch pad. Immediately after the ignition of the rocket motors, a large, hot cloud is formed near the ground, composed of carbon monoxide (CO) and carbon dioxide (CO2 ), hydrogen chloride (HCl) and also particulate material composed of aluminium oxide (Al2 O3 ) in the case of rockets driven by a solid propellant. The Weather Research and Forecasting Model (WRF), an atmospheric mesoscale model, was modified in the present study to simulate the transport, dispersion and chemistry mechanisms (with the addition of reactions involving HCl and other chlorinated compounds) of these gases released during a launch. Simulations of the dispersion of effluents were performed for different rainfall regimes (dry and rainy periods) as well as for atmospheric thermal stability (day‐ and night‐time conditions) for a specific rocket (the Veículo Lançador de Satélites, VLS) at Brazil's Alcântara Launch Center (Centro de Lançamento de Alcântara, CLA). The results show that the most critical levels of HCl and CO occurred on the launch pad (Setor de Preparação de Lançamento, SPL) from the time of the launch ( t 0 ) to 10 min. The village of Alcântara, which is 9 km from the launch pad, could be affected according to the wind direction. The concentration of HCl reached a level in the range of 2200–3800 ppmv for both dry and wet periods respectively, and these concentrations can be very hazardous to humans. Abstract : A large cloud of toxic gas, such as the one shown, is formed at the surface level a few moments after the ignition of rockets. This hot cloud expands and rapidly covers the launch pad facility and can be transported to nearby cities. In order to predict the concentrations of gases after a launch, numerical air‐quality models need appropriate methods for handling rocket emissions in order to solve this problem.